New concept of ground based-space radio interferometerand modern technologies application for deployment simulation of precise petal space reflector - Bujakas, V. I.; Glotov, M. D.
Radio interferometers make it possible to achieve high resolution of astronomical observations due to the large base of the measuring instrument. The ground-space radio telescope RadioAstron holds the record for angular resolution among radio interferometers, its maximum base was about 340 000. km. The project turned out to be very successful. The new concept is based on the experience of the RadioAstron project and proposes the use of several orbiting radio telescopes that work together in the cm and mm spectral regions. This will further increase the base of the radio interferometer and expand the viewing angle at each current moment of time. Modern technical means make it possible to launch into orbit several identical mirrors operating in the short-wavelength region of the spectrum with an effective area no worse than the effective area of the RadioAstron antenna at a wavelength of 1.35 cm. Thus, the project can be quite budgetary. Now 3D modeling and 3D printing technologies make it possible to speed up and simplify the development of physical models. The manufacture of complex parts used to take days of work. Now we can use 3D printing to make different parts in a matter of hours. In the physical model of a new petal mirror project, we used FDM and LCD printing technologies. The paper discusses examples of manufacturing petal mirror physical model components, limitations and features of these technologies.
Keywords: Astrometry; Space Sciences; Archaeoastronomy and Astronomy in Culture